FACTORS RELATING TO SEXUAL BEHAVIOR IN ADOLESCENTS AT AL-IRSYAD AL-ISLAMIYYAH MIDDLE SCHOOL SEMARANG CITY - Nabila, Idras; Octaviani, Dhita Aulia; Nugraheni, Intan (Journal of Applied Health Management and Technology, 2022)
ABSTRACTHIV / AIDS pandemic is worldwide has infected an estimated 36.9 million people. Data from the Indonesian Ministry of Health that reported new HIV-positive cases in 2018 were 46,659 cases and AIDS 10,190 cases from 34 provinces in Indonesia. Adolescence begins to feel sexual urges as shown by attraction towards the opposite sex. As a result, teenagers experiment with sexuality. The population of Indonesia is 265 million people, 18% of whom are teenagers. The highest group of adolescents aged 10-14 years amounted to 22.8 million. Adolescents are very at risk of sexual behavior and HIV / AIDS.The purpose of this study was to describe and analyze the relationship between adolescent characteristics including gender, knowledge level of reproductive health, access to information, and the role of peers on adolescent sexual behavior.This research was conducted at SLTP Al-Irsyad Al-Islamiyyah, North Semarang District, Semarang City. This type of research was quantitative using correlation analysis with a cross-sectional design. The population of this study was 235 students at Al-Irsyad Al-Islamiyyah Junior High School. Sampling with purposive sampling of 70 respondents.The results of this study indicate that there was a relationship between gender characteristics, knowledge of reproductive health on adolescent sexual behavior, with a significance p-value <0.05. There is no relationship between access to information, and the role of peers on adolescent sexual behavior with a significance p-value> 0.05. From the research results, it is hoped that the Health Officer and the Education Office can work together in monitoring and education related to adolescent reproductive health by providing education and provision of reproductive health materials. Keywords: Gender characteristics; reproductive health knowledge; access to information; the role    of peers; and adolescent sexual behavior